Two feasible ways to implement a revenue neutral Citizen's Income scheme - Malcolm Torry (University of Essex, Institute for Social and Economic Research (ISER), 2015)
A Citizen's Income - an unconditional and nonwithdrawable income for every individual - would offer many advantages, but because the UK's current benefits and tax systems are complex, transition to a benefits system based on a Citizen's Income could be difficult to achieve. This paper builds on the results contained in a previous EUROMOD working paper 2 by proposing two financially feasible ways of implementing a Citizen's Income. The first method would be an 'all at once' method. That is, it would establish a small Citizen's Income for every citizen of the UK, of whatever age. This paper shows that a strictly revenue neutral scheme is available that could be paid for by raising Income Tax rates by 3%, by abolishing Income Tax Personal Allowances, and by making adjustments to National Insurance Contributions. This scheme would impose almost no household disposable income losses on low income households at the point of implementation, and manageable losses on households in general. A second method - a 'one step at a time' method - would turn Child Benefit into a Child Citizen's Income, then establish a Young adult Citizen's Income, and then enable those in receipt of the Young adult Citizen's Income to keep their Citizen's Incomes as they grow older. This method of implementation would impose almost no losses in household disposable income at the point of implementation. The paper concludes that both 'all at once' and ''one step at a time' methods would be financially feasible.
Keywords: C80; H53; H55; I38; R20; 330; citizen's Income; household income; initial losses; microsimulation model